2019
DOI: 10.4014/jmb.1809.09021
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characterization of Phosphotransferase-Encoding Genes istP and forP as Interchangeable Launchers of the C3��,4��-Dideoxygenation Biosynthetic Pathway of 1,4-Diaminocyclitol Antibiotics

Abstract: Aminoglycosides (AGs) are the first and foremost classical antibiotics that are biosynthesized by attachment of amino-sugar units via glycosidic bonds to aminocyclitol derivatives [1]. They are recognized to inhibit prokaryotic protein synthesis by binding to the 16S rRNA subunit of the 30S bacterial ribosome, thus causing irreversible bactericidal effects against the pathogens [2]. According to the chemical features of the aminocyclitol moiety and the core aglycone unit, AGs have been categorized into well-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…AMEs exist in both resistant pathogens and AGA producers [ 33 ]. It has been speculated that these enzymes may perform other metabolic functions [ 22 ]. In the present study, we have demonstrated that gentamicin producers evolved a smart strategy to evade APH(3′) deactivation by pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMEs exist in both resistant pathogens and AGA producers [ 33 ]. It has been speculated that these enzymes may perform other metabolic functions [ 22 ]. In the present study, we have demonstrated that gentamicin producers evolved a smart strategy to evade APH(3′) deactivation by pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…CAF31545.1), while ForP can complement mutants in the dehydroxylation process of the fortimicin A biosynthesis pathway. Therefore, it is speculated that GenP can phosphorylate JI-20A, JI-20Ba, and JI-20B, which are the starting compounds of the C-3′,4′-dideoxygenation biosynthetic process [ 22 ].…”
Section: Introductionmentioning
confidence: 99%